PENGARUH PROFITABILITAS, STRUKTUR ASET, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Nabilla Ayuningtyas, Liana Susanto (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of profitability, asset structure, firm size, and liquidityoncapital structurein manufacturing industries  listed  in  Indonesian  Stock  Exchange  during  the  period  of  2015-2017.  This research used 66samples of manufacturing companies that have been previously selected using purposive sampling method for three years. The data used were secondary data in the form  of  financial  information  from  the  financial  statements  and  annual  reports.  This research  data  was  processed  using  EViews  10.  The  result  of  this  research  shows  that liquidity has an effect on capital structure, while profitability, asset structure,and  firm size does not have an effect on capital structure. Suggestion that can be given for the future research is to use other independent variables, such as non-debt tax shield.